Subsidies and Levies as Policy Instruments to Encourage Employer-Provided Training - Müller, Normann (OECD Education Working Papers, 2012)
This paper provides an overview of the available information concerning selected policy instruments intended to promote employer-provided training, including the stated rationale and objectives, the target groups and operational design as well as a at a summary of the evaluative evidence regarding their operation. The analysis focuses on policy instruments providing financial assistance or incentives, specifically, subsidies (including tax incentives and grants) and levy schemes that devote a least some share of their resources to continuing training. Training leave regulations are considered only to the extent that they can be treated as a form of subsidy or a levy scheme, depending on the main financing mechanism involved. Instruments that focus solely on improving the quality of training or enhancing transparency in the training market are not addressed. In addition to offering a description of different instruments, the paper discusses the strengths and weaknesses (or risks and opportunities, respectively) of different types of instrument or particular elements of instrument design. It also specifies principles of successful instrument design that have been put forth in the literature and concludes with some remarks regarding the choice of policies